Perilaku Kepemimpinan Teknologi Digital Dalam Dunia Pendidikan - Septiantia, Ajeng; Kadir, Ali Firdaus Abdul; Benawa, Ben; Indriana, Effi; Effendi, Rida (Diversity: Jurnal Ilmiah Pascasarjana, 2023)
Human resource empowerment (HR) is directed at increasing HR participation in organizations and increasing productivity. The results of various studies show that HR is a productivity determinant. HR in the field of school level education can be grouped into three, namely the principal, teacher, and bag. School competitiveness is also determined by HR owned. Digital leadership is also known as e-leadership or electornic leadership which was introduced by Avolio, Kahai, and Dodge contained in the scientific article E-Leadership Implications for theory, Research, and Practice. According to the article, e-leadership occurs in the context of e-envoronment where work is done through information technology, especially internet use. Research refers to the research method or commonly called Reseach and Development which is a type of research that is generally widely used in the world of education. In general, the definition of development research can be interpreted as a scientific way to obtain data so that it can be used to produce, develop and validate products. Based on the research, it can be concluded that there is an influence on learning leadership, leadership of change, spiritual leadership, school culture, and professional ethics of the performance of teaching school teachers. Keywords: Leadership, Education, Digital Technology